Tecniche di rilievo integrate applicate ad architetture complesse e degradate - D'Auria, Saverio; De Silla, Fabrizio; Gabrielli, Roberto; Strollo, Rodolfo Maria (Archeomatica, 2016)
The paper presents methodologies and specific technologies connected to research activities of LAREA (LAboratorio di Rilievo E Architettura/Laboratory of Survey and Architecture) of University of Roma Tor Vergata in cooperation with ITABC (Istituto per le Tecnologie Applicate ai Beni Culturali) of CNR. The goal of this case study is to contribute to the 3D digital documentation of Villa Mondragone in Monte Porzio Catone (Rome).In particular, the research is aimed to integrating laser scanning, digital photogrammetry and thopographic survey of Ninfeo, a monumental and scenographic artifact located at one end of the Giardino della Girandola, characterized by an articulated architecture and detailed decorations.